Efficacy and Safety of Low-Dose Peginterferon Alpha-2a Plus Ribavirin on Chronic Hepatitis C. (3rd December 2012) - Yan, Zehui; Fan, Ke; Wang, Xiaohong; Mao, Qing; Deng, Guohong; Wang, Yuming
Abstract : Background . The purpose of this study was to assess the efficacy and safety of low-dose peg-IFN α -2a plus ribavirin on the treatment of patients with chronic hepatitis C virus (HCV) infection. Patients and Methods . A total of 243 HCV patients treated with different doses of peg-IFN α -2a plus ribavirin were stratified into three groups. End-of-treatment response (ETR) and sustained viral response (SVR) were evaluated for efficacy. Adverse events and laboratory abnormalities were conducted for safety. Results . ETR and SVR in group I were obtained in 83.9% and 68.9% of the patients, separately, which was similar to groups II (84.1% and 68.3%) and III (81.7% and 66.7%). The received peg-IFN α -2a dose was not the independent factor-related SVR in our population (OR, 1.31; 95% CI, 0.94–1.81; P = 0.106 ). The frequency of no adverse events reported in group III (24.7%) was significantly higher than that in group I (11.5%) and group II (12.7%) (P = 0.036 ). Conclusions . The peg-IFN α -2a 90 μ g/week plus ribavirin is as effective as, and better tolerated than, peg-IFN α -2a standard dose with ribavirin in the treatment of chronic hepatitis C. This low-dose combination achieves high SVR rates and may be cost-saving.